Interview with the fashion business and management working group coordinators: Maya Marx Estarque and Flávio Sabrá (Revista de Ensino em Artes, Moda e Design, 2023)
Interview conducted by the editors of Revista de Ensino em Artes, Moda e Design.
Keywords: Fashion; Manegement; Design; Business